Urgence of Special Education for Commissioners of the Consumer Dispute Settlement Agency (BPSK) - Anak Agung Sagung Laksmi Dewi (Sociological Jurisprudence Journal, 2023)
Progress in science and technology, including telecommunications and information, have resulted in an increase in the variety and quality of the production of goods and services, including an increase in the space for transactions that cross national boundaries. The aims research is to know what are the methods of problem solving by the Consumer Dispute Settlement Agency and to know what is the urgency of special education for commissioners of the Consumer Dispute Settlement Agency. The result shows that The Consumer Dispute Settlement Agency has the duties and authorities as stipulated in Article 52 UUPK and the Decree of the Minister of Industry and Trade Number 350/MPP/Kep/12/2001, dated December 10, 2001, concerning the Implementation of the Duties and Authorities of the Consumer Dispute Settlement Agency, namely carrying out the handling and settlement of consumer disputes by conciliation, mediation, and arbitration. To support the performance of The Consumer Dispute Settlement Agency members, which consists of three different elements, special education, and training are needed to build the professionalism of The Consumer zDispute Settlement Agency members. Considering that The Consumer Dispute Settlement Agency itself has the scope of authority to resolve consumer disputes using conciliation, mediation, and arbitration, it can support the effectiveness of The Consumer Dispute Settlement Agency 'S performance in resolving issues related to consumer disputes.